Implicit Large-Eddy Simulations of Wall-Bounded Turbulent Flows. - Drikakis, Dimitris; Hahn, Marco; Malick, Zeshan; Shapiro, Evgeniy (Cranfield University, 2007)
The paper presents application of Implicit Large Eddy Simulation(ILES)to wall- bounded turbulent flows. A characteristics-based scheme in conjunction with total variation diminishing(TVD)Runge-Kutta time stepping and slope-limiting variants,for the com-pressible flow case, have been employed. Results are pre- sented for an incompressible lid-driven cavity flow,using an incompressible solver, and low-Mach number flows over a hill and around a delta wing, using a compressible solver. Good agreement with experimental data and numerical results using classical LES has been obtained. Future ILES developments are also discussed